Pengaruh Lingkungan Fisik dan Waktu Antri Terhadap Kepuasanan Nasabah Bank Papua Cabang Serui Kabupaten Kepulauan Yapen - Rinaldo Piris (Journal on Education, 2023)
This study aims to determine the effect of the physical environment and queuing time on customer satisfaction at Bank Papua Serui Branch. The population used is all customers who use the services of Bank Papua Serui Branch, while the sample used is as many as 100 people using the convenience sampling method, namely samples taken from members of the population who are easily available to provide information. The data collected was sourced from primary data, namely Bank Papua Serui Branch customers through distributed questionnaires and secondary data, namely agencies related to this research. The data analysis method used is important-performance analysis (IPA), and statistical analysis using the SPSS 21 For Windows program. Based on the results of the analysis it was found that: 1) the degree of conformity between the interests/expectations of the consumer towards the physical environment and the actual performance/implementation is 79.21% indicating that the customer is satisfied, 2) the degree of compatibility between the expectations/interests of the customer regarding the queue time and the actual performance/ .implementation shows that the customer is quite satisfied, 3) The results of the analysis using regression analysis and multiple correlations show that there is a positive and significant influence between the physical environment and queuing time on customer satisfaction, 4) the results of testing using the T-Test and F-Test statistics also shows that there is a positive and significant influence between the physical environment and queuing time on customer satisfaction, both tests are carried out partially or simultaneously.